PENGEMBANGAN MEDIA E-BOOK INTERAKTIF UNTUK MATA PELAJARAN TEKNIK MIKROPROSESOR DI SMK NEGERI SURABAYA - Imansari, Nurulita; Buditjahjanto, I.G.P Asto (PENDIDIKAN VOKASI:TEORI DAN PRAKTIK, 2014)
ABSTRACT The research aimed : 1) to create a valid interactive e-book as learning media for Microprocessor Technique at SMKN Surabaya, 2) to find the difference of student learning result between students who are taught by interactive e-book and students who are taught by PowerPoint, 3) to know the student?s responses on the use of interactive e-book as a learning media. The research method used 4-D model. The research was conducted under quasi experimental design with intact group comparison which was comparing two groups. The design of the experiment class used an interactive e-book but the control class used a power point media. Both groups were given posttest. The results found that the average of the data was 79,2% so it is categorized as valid, the posttest exercise categorized as valid and has average 76,5%. The student learning results in experiment class has average value 82,15 but the control class has average value 77,15. The student learning results from experiment class and control class were compared using a t-test. From the student learning result we got t count is 3,824 and the t test is 1,658. Its means that t count>t test so the student learning result using interactive e-book was better than using PowerPoint media. The student?s responses toward interactive e-book categorized was very good and valid to be used in learning process. Keywords : Interactive E-Book, Student Learning Result